Assessment of Physical Deconditioning due to COVID-19 Lock Down: A Comparison between COVID-19 Affected and Non-affected Person (Medicine Today, 2025)
Introduction: The COVID-19 lockdown significantly reduced physical activity due to home confinement and limited access to fitness facilities, leading to physical deconditioning characterized by decreased strength, endurance, and mobility. Those infected with COVID-19 may have experienced more severe deconditioning due to illness-related inactivity, respiratory issues, and prolonged recovery, particularly in long-COVID cases. Objectives: To find out the physical deconditioning pattern due to lock down. Materials and Methods: This is a Case-control Study carried out Post COVID-19 clinic and Department of Physical medicine & rehabilitation in BSMMU during the period of 01-7-2021 to 30-06-2022. The patients (As Case) attending in post COVID-19 clinic at OPD of BSMMU and persons (As Control) attending the OPD. The subjects were divided into two groups as designated below: Group A: The case group was COVID-19 positive previously and Group B: Control group was the normal individual. So, total sample size is 150 in each group. The data was collected by semi structured questionnaire. The data was analyzed statistically by using Statistical Package for Social Science (SPSS) for Windows version 23. Results: Most participants were in service (98, 30.1%), housewives (81, 24.8%), businessmen (37, 11.3%), and physicians (28, 8.6%), with 82 (25.2%) from various other occupations like garment workers, students, teachers, and bankers. The case group showed mostly mild to moderate fatigue, while the control group had mild or no fatigue (P=0.001). In cases, most had Grade-1 & 2 dyspnea by MMRC, while the control group had Grade-0, 1, & 2. Deconditioning in activities like feeding, dressing, and grooming was common in cases but rare in controls (P=0.001). Personal hygiene deconditioning was mild to moderate in cases, while 108 controls had none, and 63 had mild issues (P=0.001). Moderate deconditioning was common in cases for outlet and active recreation, while controls had no deconditioning. Cases also showed mild to moderate deconditioning in socialization, whereas controls had no or mild deconditioning (P=0.001). Conclusion: This study concluded that deconditioning symptoms were more severe in COVID-19 patients compared to non-infected individuals. Fatigue and dyspnea were common, especially in those with co-morbidities. Daily activities were more significantly affected in COVID-19 patients. Exercise is recommended during lockdowns to reduce physical deconditioning.Medicine Today 2025, Vol.37 (1): 27-32